Appraisal of Engagement in Les Brown Speech’s Enough is Enough - Eminently Ziliwu (Talenta Publisher, 2020)
This paper concentrated on the appraisal engagement used in Les Brown Speech’s Enough Is Enough. The questions posed by this study relate to what type of engagement is found in this speech, and (2) how is the engagement realized in the speech. The study adopts a qualitative analysis to identify engagement used in the text ‘Enough Is Enough’.The findings showed that there were monoglossic 45 (18,90%) and heteroglossic 193 (81,10%) which consist of contraction: disclaim 103 (43,27%), proclaim 51 (21,43%) and expansion: entertain 38 (15,97%), attribute 1 (0,42%). The dominantly used contraction in heteroglossic system showed that the speaker conveyed propositions and proposals that contain definite and firm meaning in order to motivate the listeners. In conclusion, the most dominant type which found in disclaim namely ‘deny’ is used to give command to the listeners not to do something in vain.